Fluorescence Spectral Properties of 2,5-Diphenyl-1,3,4-oxadiazole with Two-Color Two-Photon Excitation - Lakowicz, Joseph R. (J Phys Chem, 1996)
We observed fluorescence emission from 2,5-diphenyl-1,3,4-oxadiazole (PPD) resulting from two-photon excitation with two different wavelengths near 380 and 760 nm. For this two-color two-photon (2C2P) excitation the emission spectra and intensity decays were the same as observed with single-photon excitation with an equivalent energy at 250 nm. The two-color two-photon-induced emission was observed when the PPD sample was illuminated with both wavelengths, but only when the picosecond laser pulses were spatially and temporally overlapped. The signal was about 70-fold and 1000-fold less for illumination at 380 or 760 nm alone, respectively. When illuminated with both wavelengths, the emission intensity of PPD depended quadratically on the total illumination power, when both beams were simultaneously attenuated to the same extent, indicating two-photon excitation. When the intensity at one wavelength was attenuated, the signal depended linearly on the power at each wavelength, indicating the participation of one-photon at each wavelength to the excitation process. For 2C2P excitation the time-zero anisotropy was larger than possible for single-photon excitation and was consistent with collinear electronic transitions for both wavelengths. The intensity depended on the polarization of each beam in a manner consistent with collinear transitions. These results demonstrate that two-color two-photon excitation can be readily observed with modern laser sources. This phenomenon can have numerous applications in the chemical and biomedical sciences, as a method for spatial localization of the measured volume.